Discrimination, other psychosocial stressors, and self-reported sleep duration and difficulties - Slopen, Natalie; Williams, David R (Sleep (New York, N.Y.), 2014)
To advance understanding of the relationship between discrimination and sleep duration and difficulties, with consideration of multiple dimensions of discrimination, and attention to concurrent stressors; and to examine the contribution of discrimination and other stressors to racial/ ethnic differences in these outcomes. Cross-sectional probability sample. Chicago, IL. There were 2,983 black, Hispanic, and white adults. Outcomes included self-reported sleep duration and difficulties. Discrimination, including racial and nonracial everyday and major experiences of discrimination, workplace harassment and incivilities, and other stressors were assessed via questionnaire. In models adjusted for sociodemographic characteristics, greater exposure to racial (β = -0.14)) and nonracial (β = -0.08) everyday discrimination, major experiences of discrimination attributed to race/ethnicity (β = -0.17), and workplace harassment and incivilities (β = -0.14) were associated with shorter sleep (P < 0.05). The association between major experiences of discrimination attributed to race/ethnicity and sleep duration (β = -0.09, P < 0.05) was independent of concurrent stressors (i.e., acute events, childhood adversity, and financial, community, employment, and relationship stressors). Racial (β = 0.04) and non-racial (β = 0.05) everyday discrimination and racial (β = 0.04) and nonracial (β = 0.04) major experiences of discrimination, and workplace harassment and incivilities (β = 0.04) were also associated with more (log) sleep difficulties, and associations between racial and nonracial everyday discrimination and sleep difficulties remained after adjustment for other stressors (P < 0.05). Racial/ethnic differences in sleep duration and difficulties were not significant after adjustment for discrimination (P > 0.05). Discrimination was associated with shorter sleep and more sleep difficulties, independent of socioeconomic status and other stressors, and may account for some of the racial/ethnic differences in sleep.